2002
DOI: 10.1128/iai.70.10.5740-5750.2002
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Targeting ofPorphyromonas gingivalisW50 Protease in Epithelial Cells

Abstract: Porphyromonas gingivalis is an important pathogen associated with destructive periodontal disease and is able to invade the epithelial cell barrier. Its cysteine proteases are recognized as major virulence factors, and in this study, we examined the interaction of the arginine-specific protease with epithelial cells in culture. Three cell lines (KB, HeLa, and SCC4) were incubated with strain W50 culture supernatant; stained with monoclonal antibody 1A1, which recognizes an epitope on the adhesin (␤) component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
4
33
0
Order By: Relevance
“…A recent study with chimeric constructs of human PECAM-1 revealed that homophilic binding of PECAM-1 on adjacent cells and positively charged sequences ( 599 RKAKA K 604 ) in the juxtamembrane region of the transmembrane domain of PECAM-1 are important for its localization to cell-cell borders (62). In this context, the hemagglutinin domains have been reported to regulate intracellular dispersion of gingipains taken up by epithelial cells (57), and the proteinases have specificity for arginine and lysine residues (54), with the 599 RK AKAK 604 sequence a potential target. The major proteinase inhibitors present in human serum are alpha-1-antitrypsin, alpha-1-antichymotrypsin, and alpha-2-macroglobulin (␣ 2 M).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with chimeric constructs of human PECAM-1 revealed that homophilic binding of PECAM-1 on adjacent cells and positively charged sequences ( 599 RKAKA K 604 ) in the juxtamembrane region of the transmembrane domain of PECAM-1 are important for its localization to cell-cell borders (62). In this context, the hemagglutinin domains have been reported to regulate intracellular dispersion of gingipains taken up by epithelial cells (57), and the proteinases have specificity for arginine and lysine residues (54), with the 599 RK AKAK 604 sequence a potential target. The major proteinase inhibitors present in human serum are alpha-1-antitrypsin, alpha-1-antichymotrypsin, and alpha-2-macroglobulin (␣ 2 M).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have observed that a high concentration of Kgp can cause BCAEC detachment and apoptosis (our unpublished observations) suggesting that there is a threshold level of gingipain activity below which a cell can remain viable, but at gingipain activity above this level the cell cannot overcome gingipain-induced effects and becomes apoptotic. This threshold phenomenon has been demonstrated in epithelial cells treated with HRgpA (175).…”
Section: Apoptosis Can Occur With and Without Caspase Involvementmentioning
confidence: 90%
“…HRgpA localizes to the nucleus (175) and may be able to cleave lamin B and subsequently gain access to the nucleus to cleave Topo I and possibly modulate other nuclear proteins, producing the nuclear apoptotic morphology. Kgp may function similarly to and work with HRgpA, since its nuclear targeting ability was not dependent on proteolytic activity (175). Figure 5 is a comparison of potential caspaseindependent apoptosis pathway members induced by gingipain activity.…”
Section: Caspase-independent P Gingivalis -Induced Apoptosismentioning
confidence: 99%
“…Based on karyotyping, the HEp-2 cell line has been reclassified as HeLa (44). Both cell lines have been used extensively to study host-bacterial interactions, including those with P. gingivalis (5,9,45,46), and, in the present study, we used HEp-2 cells to maintain consistency with previous work (7,17). The mouse NIH/3T3 fibroblast cell line was purchased from the American Type Culture Collection (ATCC) and cultivated in DMEM supplemented with 10% FCS.…”
Section: Methodsmentioning
confidence: 99%
“…gingivalis binds to several human cell types and is internalized upon attachment; adherence and entry are mediated by bacterial surface structures such as fimbriae (5,6) and gingipain cysteine proteinases (7)(8)(9). A number of surface components of eukaryotic cells have been suggested to serve as receptors.…”
mentioning
confidence: 99%